'No "Sane" Person Would Have Any Idea': Patients' Involvement in Late Nineteenth-century British Asylum Psychiatry. Issue 1 (10th December 2015) - Chaney, Sarah
Abstract : In his 1895 textbook, Mental Physiology, Bethlem Royal Hospital physician Theo Hyslop acknowledged the assistance of three fellow hospital residents. One was a junior colleague. The other two were both patients: Walter Abraham Haigh and Henry Francis Harding. Haigh was also thanked in former superintendent George Savage's book Insanity and Allied Neuroses (1884). In neither instance were the patients identified as such. This begs the question: what role did Haigh and Harding play in asylum theory and practice? And how did these two men interpret their experiences, both within and outside the asylum? By focusing on Haigh and Harding's unusual status, this paper argues that the notion of nineteenth-century 'asylum patient' needs to be investigated by paying close attention to specific national and institutional circumstances. Exploring Haigh and Harding's active engagement with their physicians provides insight into this lesser-known aspect of psychiatry's history. Their experience suggests that, in some instances, representations of madness at that period were the product of a two-way process of negotiation between alienist and patient. Patients, in other words, were not always mere victims of 'psychiatric power'; they participated in the construction and circulation of medical notions by serving as active intermediaries between medical and lay perceptions of madness.